2014
DOI: 10.1590/1983-1447.2014.04.45491
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of job satisfaction of the nursing staff of a primary health care unit

Abstract: This was a cross-sectional, observational study conducted in an outpatient specialty district health unit in the city of Ribeirão Preto, in the southeastern Brazilian state of São Paulo, with the aim to analyze the job satisfaction of the nursing staff. Data were collected using the Index of Work Satisfaction (IWS), a validated instrument which was applied to 23 members of the nursing team in January 2012. Among the components of job satisfaction, participants considered Interaction to be most important, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
5

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
6
0
5
Order By: Relevance
“…Strategies to include nurses in administration and commissions, together with offering training and opportunities to contribute to the institution's decision-making favors the autonomy of these professionals and such inclusion in increases satisfaction with Organizational Policies (18) . The true state of professional satisfaction points to the importance of Interactions both for the nursing team and the nursing technicians/auxiliaries, as has been reported in the literature (15,19) . While the least valorized component among the nurses is Autonomy, again in corroboration with other research (7,11) .…”
Section: Discussionmentioning
confidence: 53%
“…Strategies to include nurses in administration and commissions, together with offering training and opportunities to contribute to the institution's decision-making favors the autonomy of these professionals and such inclusion in increases satisfaction with Organizational Policies (18) . The true state of professional satisfaction points to the importance of Interactions both for the nursing team and the nursing technicians/auxiliaries, as has been reported in the literature (15,19) . While the least valorized component among the nurses is Autonomy, again in corroboration with other research (7,11) .…”
Section: Discussionmentioning
confidence: 53%
“…The weighed IWS score found in this study (10.95 points) is in the 2 nd quartile and close to the 50th percentile, indicating low work satisfaction. Other Brazilian studies performed in ICUs and emergency units found even lower IWSs -9.6 (8) and 8.29 (18) , respectively -also showing low work satisfaction in the samples investigated.…”
Section: Discussionmentioning
confidence: 56%
“…Such characteristics are cited as promoting occupational stress and are defined as important elements that negatively affects the work process, harming it (19) . Besides that, in the nursing work, is it observed the presence of professionals with more than one employment bond due to the low salaries earned and to the low minimum wage considering 44 hours worked per week (20)(21)(22) . Another study has verified that there were double employment bond in 72% of nursing workers studied, against 28% having only one employment bond (12) .…”
Section: Discussionmentioning
confidence: 99%